2012
DOI: 10.1080/02664763.2011.644529
|View full text |Cite
|
Sign up to set email alerts
|

The internal relocation premium: are migrants positively or negatively selected? Evidence from Italy

Abstract: Abstract• : This paper analyzes the wage returns from internal migration for recent graduates inItaly. We employ a switching regression model that accounts for the endogeneity of the individual's choice to relocate to get a job after graduation: the omission of this selection decision can lead to biased estimates, as there is potential correlation between earnings and unobserved traits exerting an influence on the decision to migrate. The empirical results sustain the appropriateness of the estimation techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
2
0
5
Order By: Relevance
“…Then, we decided not to use both variables as instruments for all countries, but we choose the better instrument case by case. Following the suggestion of Cutillo and Ceccarelli (2010), we checked the validity of the instruments by using the approach proposed by Dolton and Vignoles (2002). According to these authors, a valid instrument must be uncorrelated with the error term of the outcome equation, and thus it should not affect the risk of overeducation conditional on the included explanatory variables.…”
Section: Young_children Dummies)mentioning
confidence: 99%
“…Then, we decided not to use both variables as instruments for all countries, but we choose the better instrument case by case. Following the suggestion of Cutillo and Ceccarelli (2010), we checked the validity of the instruments by using the approach proposed by Dolton and Vignoles (2002). According to these authors, a valid instrument must be uncorrelated with the error term of the outcome equation, and thus it should not affect the risk of overeducation conditional on the included explanatory variables.…”
Section: Young_children Dummies)mentioning
confidence: 99%
“…O Quadro 01 apresenta as variáveis selecionadas, dependentes e explicativas de controle empregadas no modelo. Ressalta-se que tais variáveis refletem aspectos da dinâmica socioeconômica e demográfica no território, e foram escolhidas com base na literatura que estuda o tema (MINCER, 1978;HECKMAN, 1979;FREGUGLIA, 2007;CUTILLO;CECCARELLI, 2012;GAMA;MACHADO, 2014;SILVA FILHO, 2017;SILVA;CAVALCANI;SILVA FILHO, 2019).…”
Section: Procedimentos Metodológicosunclassified
“…Porém, a Capital Federal e as capitais dos demais Estados do Centro-Oeste mostraram-se atrativas ao ingresso da força de trabalho migrante na década de 2000. Isso já era esperado, uma vez que a busca por melhores condições de vida fazem com que os indivíduos migrantes, mais determinados e persistentes que indivíduos não migrantes com características socioeconômicas observáveis semelhantes, migrem para essas cidades (BORJAS, 1987;DUSTAMANN;GLITZ, 2011;CUTILLO;CECCARELLI, 2012).…”
Section: Figura 1: Saldo Migratório Da Força De Trabalho Ocupada Nos Municípios Dounclassified
“…They found that migration for work is the most relevant driver of wage premium; considerably smaller is the contribution of migration for study and even negative the effect on wages of the “go back home” pattern of mobility following an initial mobility for study. In the same vein, Cutillo and Ceccarelli () analysed the wage returns from internal migration for a sample of graduates. They documented positive self‐selection into migration arguing that movers are likely to be more motivated and able than their peers.…”
Section: Literature Reviewmentioning
confidence: 99%